PENGARUH PERUBAHAN ORGANISASI TERHADAP PERILAKU KERJA, IKLIM ORGANISASI DAN KINERJA KARYAWAN (Studi Pada Balai Besar Wilayah Sungai Serayu-Opak Direktorat Jenderal Sumber Daya Air Departemen Pekerjaan Umum) - Utomo, Hariyono (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2011)
The Technical Implementation Unit formation into the form of Central River Region leads to changes in the physical and structural aspects of the organization which would affect the changes in systems and procedures, employee behavior and organizational climate and culture. These changes will affect the performance of the organization after the institutional restructuring. Based on these empirical phenomena it is necessary to study about the effect of organizational change on the changes in work behavior, organizational climate and employee performance.Therefore we conducted various studies on the theories that explain the changes in organization, work behavior, organizational climate and performance of employees and review of the results of previous studies to determine the effect of each variable between studies. Based on these studies led us to develop a research model consisting of four research hypotheses.The hypothesis testing is done by using analytical techniques: Structural Equation Modeling (SEM) with primary data which include organizational change, work behavior, organizational climate and employee performance. The primary data obtained through interviews with 105 employees of Central River Region tor Serayu Opak.The results showed that the model developed is a fit model or no difference between the predicted model based on sample data with the population and the results of hypothesis testing showed that organizational change is proven to have a positive and significant impact on employee behavior, organizational change has a positive and significant impact on organizational climate, employee behavior has a positive and significant impact on performance, and the hypothesis which stated that organizations climate have a positive and significant impact on performance.